2007
DOI: 10.1158/0008-5472.can-06-3530
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of IFN Regulatory Factor (IRF)-1 and IRF-2 in the Formation and Progression of Human Esophageal Cancers

Abstract: IFN regulatory factor (IRF)-1 and IRF-2 are generally regarded as a tumor suppressor and an oncoprotein, respectively. However, little is known about their expression and function in esophageal squamous cell carcinomas (ESCC). In our present work, IRF-1 expression was decreased and IRF-2 expression was increased in ESCCs compared with matched normal esophageal tissues. Moreover, statistical data indicated that IRF-2 expression was tightly correlated with progression of ESCCs. As expected, overexpression of eit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 47 publications
7
81
0
Order By: Relevance
“…Our recent results also established that both IRF-1 and IRF-2 are involved in the development and progression of ESCCs (15), but thus far, little attention has been paid to the influences of IFN-g on ESCC cells. In the present work, therefore, we studied in detail the functions of IFN-g in ESCC cells and displayed novel results that IFN-g induced the up-regulation of IRF-2 and IRF-2 attenuated the IFN-g pathway by inhibiting IFNGR1 transcription, which implied an interesting, previously undescribed, negative feedback loop for IFN-g-induced pathway.…”
Section: Introductionsupporting
confidence: 54%
“…Our recent results also established that both IRF-1 and IRF-2 are involved in the development and progression of ESCCs (15), but thus far, little attention has been paid to the influences of IFN-g on ESCC cells. In the present work, therefore, we studied in detail the functions of IFN-g in ESCC cells and displayed novel results that IFN-g induced the up-regulation of IRF-2 and IRF-2 attenuated the IFN-g pathway by inhibiting IFNGR1 transcription, which implied an interesting, previously undescribed, negative feedback loop for IFN-g-induced pathway.…”
Section: Introductionsupporting
confidence: 54%
“…Moreover, the molecular background of the growthpromoting and anti-apoptotic effects of IRF-2 has been largely substantiated by its direct stimulatory effect on the expression of histone H4, cyclin-D1 and Bcl-2 as well as by its down-regulating effect on activated caspase-9. 16,17 Here we report, however, that univariate survival analyses show not only high intratumoral IRF-1 expression but also high-level IRF-2 expression to be associated with improved disease-free and overall survival in a large cohort of 138 ovarian cancer patients. This meaningful, albeit unexpected, finding regarding IRF-2 stands in contrast to the data on solid tumors published so far.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, statistical data indicated that IRF-2 expression was tightly correlated with disease progression in esophageal cancer. 16 Moreover, besides the association between high-level IRF-2 expression and improved survival in univariate analyses, other of our findings argue against an oncogenic role of IRF-2 in ovarian cancer: (i) in contrast to other solid tumors such as diffusely infiltrating astrocytomas, breast and as already mentioned esophageal cancers, 16,18,19 the expression of IRF-2 was not found to be upregulated in either ovarian cancer tissue or established ovarian cancer cell lines, (ii) significantly higher levels of IRF-2 mRNA were found in early-stage when compared with advanced-stage ovarian cancers, and (iii) IRF-2 expression was inversely related to residual disease after primary debulking surgery. Concerning the latter point, there is excellent evidence to show that ovarian cancers, whose complete surgical clearance is impossible at primary surgery, exhibit a more aggressive phenotype with a completely different molecular signature than do cancers allowing optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…These IRF molecules play roles in antiviral defense, immunoresponse/modulation, and cell growth regulation under stimulation with IFN-␣, ␤, and ␥ (35-38). IRF-1 and -2 have been shown to act as an agonist-antagonist pair involved in the regulation of many IFN-␥-inducible genes (35)(36)(37)(38). Interestingly, IFN-␥ markedly suppressed BH mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, IRF-1/2 transcriptional factor would also be required for the minimal promoter activity of the BH gene under basal conditions. The IRF family is a group of transcription factors, and so far, nine IRF members (IRF-1-9) have been identified in various cell types and tissues (35)(36)(37)(38). These IRF molecules play roles in antiviral defense, immunoresponse/modulation, and cell growth regulation under stimulation with IFN-␣, ␤, and ␥ (35-38).…”
Section: Discussionmentioning
confidence: 99%